Biochemical and Pharmacological Characterization of YM-60828, a Newly Synthesized and Orally Active Inhibitor of Human Factor Xa - Taniuchi, Yuta; Sakai, Yumiko; Hisamichi, Nami; Kayama, Makoto; Mano, Yuji; Sato, Kazuo; Hirayama, Fukushi; Koshio, Hiroyuki; Matsumoto, Yuzo; Kawasaki, Tomihisa (Thrombosis and Haemostasis, 1998)
YM-60828 was found to potently inhibit human factor Xa following oral administration. YM-60828 showed high affinity for factor Xa (Ki = 1.3 μM), but did not affect thrombin (Ki > 100 μM). YM-60828 doubled factor Xa clotting time, prothrombin time (PT) and activated partial thromboplastin time (APTT) at 0.10, 0.21, 0.24 μM, respectively. Importantly, it did not prolong thrombin time at 100 μM. YM-60828 also inhibited factor Xa in the prothrombinase complex with an IC50 value of 7.7 nM. In addition to its anticoagulant activity, YM-60828 inhibited platelet aggregation induced by various agonists (IC50 = 3 to 23 μM). Squirrel monkeys were used to study the ex vivo anticoagulant activity and pharmacokinetic properties of YM-60828. One hour after oral administration at 3 mg/kg, YM-60828 strongly prolonged PT and APTT by 4.8- and 1.9-fold, respectively, and plasma concentration reached 788 ± 167 ng/ml. Bioavailability was calculated to be 20.3%. These results strongly suggest that YM-60828 will be a valuable orally active and potent anticoagulant agent showing potential antithrombotic activity.